(untitled) - Zhang, Jin-hua (New York, 1991)
The book covers new machining and tooling topics such as high-speed and hard-part machining, near-dry and dry-machining strategies, multi-functional tooling, ‘diamond-like’ and ‘atomically-modified’ coatings, plus many others. Also covered are subjects important from a research perspective, such as micro-machining and artificial intelligence coupled to neural network tool condition monitoring.
Keywords: Cắt kim loại,Metal-cutting